TAYM-MENEJMENT TA’LIM FAOLIYATINI SAMARALI TASHKIL ETISH VOSITASI SIFATIDA - Bekniyazov, B.S. (SCIENCE and SOCIETY, 2024)
This article describes time management tools, time management technologies and the specific features of using these technologies in the field of educational process management in the activities of general education school leaders.
Keywords: time; educational organization; leader; time management; educational technologies; educational process; educational activities; Eisenhower matrix